Investor Relations, Firm Visibility, and Investor Following - Bushee, Brian J.; Miller, Gregory S. (The Accounting Review, 2012)
ABSTRACT We examine the actions and outcomes of investor relations (IR) programs in smaller, less-visible firms. Through interviews with IR professionals, we learn that IR strategies have a common goal of attracting institutional investors and that direct access to management, rather than increased disclosure, is viewed as the key driver of the strategy's success. We test for the effects of IR programs by examining small-cap companies that hired IR firms in a differences-in-differences research design with controls for changes in disclosure and determinants of the decision to initiate IR. Relative to a matched sample of control firms, we find that companies initiating IR programs exhibit greater increases in institutional investor ownership and a shift toward investors that normally would not follow the companies. We also find greater improvements in analyst following, media coverage, and the book-to-price ratio. Our results indicate that IR activities successfully improve visibility, investor following, and market value. Data Availability: All analyses are based on publicly available data.